A highly hydrophilic and anti-stripping composite alkaline water electrolysis hydrogen production diaphragm and preparation method thereof

Through the combined preparation method of supporting wire mesh and cast film liquid, the existing hydrogen-making membrane has high surface resistance and easy peeling of inorganic particles, and a composite alkaline electrolytic hydrogen-making membrane with low surface resistance, low thickness, good hydrophilicity and wetting performance is achieved.

CN119243249BActive Publication Date: 2025-04-15JIANGSU NEW HORIZON ADVANCED FUNCTIONAL FIBER INNOVATION CENT CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411357711.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-27
Publication Date
2025-04-15
Estimated Expiration
2044-09-27

AI Technical Summary

Technical Problem

The existing problems include high resistance of the hydrogen-producing membrane surface, easy peeling of hydrophilic inorganic nanoparticles, insufficient toughness, and large thickness.

Method used

The method of preparing support wire mesh and cast film liquid is adopted. The cast film liquid contains organic solvents, alkali-resistant polymers, pore support fillers, organic hydrophilic modifiers, and pore-making agents. A composite alkaline electrolytic water hydrogen-making separator with high hydrophilicity and anti-flaking is prepared by film laying and solidification bath.

Benefits of technology

The low surface resistance, low thickness, good hydrophilicity and wetting properties of the diaphragm are achieved, and the problems of inorganic particles peeling and diaphragm fracture are avoided, and it has great application potential and promotion value.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119243249B_ABST
    Figure CN119243249B_ABST
Patent Text Reader

Abstract

The present invention relates to a highly hydrophilic and anti-stripping composite alkaline water electrolysis hydrogen production diaphragm and a preparation method thereof, which belongs to the technical field of alkaline water electrolysis hydrogen production diaphragm, and solves at least one of the problems of high surface resistance of hydrogen production diaphragm, easy peeling of hydrophilic inorganic nanoparticles, insufficient toughness, large thickness, etc. in the prior art. The present invention discloses a preparation method of alkaline water electrolysis hydrogen production diaphragm, wherein the supporting screen is paved with a casting liquid, and then subjected to a coagulation bath to obtain the diaphragm; the casting liquid contains an organic solvent, an alkali-resistant polymer, a pore support filler, an organic hydrophilic modifier, and a pore-forming agent. The hydrogen production diaphragm does not contain inorganic particles, and has the characteristics of high hydrophilicity, high wettability, good flexibility, low surface resistance, etc. The thickness can be as low as 100 microns, the preparation process is simple, and it is suitable for large-scale application and wide promotion.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of alkaline water electrolysis hydrogen production diaphragms, and in particular to a highly hydrophilic and anti-stripping composite alkaline water electrolysis hydrogen production diaphragm and a preparation method thereof. Background Art

[0002] For a long time, people have used traditional fossil energy as the main energy source, which has caused a series of problems, such as high greenhouse gas emissions causing global warming and pollutant emissions causing severe environmental pollution. With the proposal of the dual carbon goals, the development of clean and efficient renewable energy has become a global consensus. Hydrogen energy is an ideal secondary energy source and a good clean energy carrier. Converting abandoned wind and solar energy into hydrogen energy for storage and utilization has become a feasible technical route.

[0003] At present, the main production method of green hydrogen is to prepare hydrogen through alkaline water electrolysis tanks. Alkaline electrolysis tanks are mainly composed of plates, diaphragms and alkaline electrolytes. The diaphragms mainly isolate hydrogen and oxygen while ensuring high water permeability and ion permeability, which plays a decisive role in the purity of the produced hydrogen and reducing power consumption. Early electrolysis tanks mainly used asbestos diaphragms, which were gradually replaced due to environmental and carcinogenic issues.

[0004] At present, PPS fabric diaphragms or inorganic-polymer composite diaphragms are generally used as hydrogen production diaphragms. However, this type of diaphragm is easily broken and damaged during transportation and installation, which leads to the scrapping of the diaphragm. The thickness of the diaphragm is also limited, mostly around 500 microns, and it is impossible to make it thinner, which leads to the inability to obtain a lower surface resistance. Summary of the invention

[0005] In view of the above analysis, the embodiments of the present invention aim to provide a highly hydrophilic and anti-peeling composite alkaline water electrolysis hydrogen production diaphragm and a preparation method thereof, so as to solve at least one of the problems of the existing hydrogen production diaphragm, such as high surface resistance, easy peeling of hydrophilic inorganic nanoparticles, insufficient toughness, and large thickness.

[0006] The invention discloses a method for preparing a diaphragm for producing hydrogen by alkaline water electrolysis, wherein a supporting screen is paved with a film casting liquid and then subjected to a coagulation bath to obtain the diaphragm;

[0007] Wherein, the supporting wire mesh is woven from alkali-resistant high-strength polymer monofilaments;

[0008] The casting solution contains an organic solvent, an alkali-resistant polymer, a pore supporting filler, an organic hydrophilic modifier and a pore-forming agent.

[0009] The preparation method comprises the following specific steps:

[0010] S1: preparing a support screen and measuring an organic solvent, an alkali-resistant polymer, a pore support filler, an organic hydrophilic modifier, and a pore-forming agent according to a preset formula;

[0011] S2: dissolving the pore-forming agent in an organic solvent, slowly adding the pore support material under ultrasonic and stirring conditions to make it uniformly dispersed without sedimentation; adding an alkali-resistant polymer and ensuring that it is completely dissolved; finally adding an organic hydrophilic modifier and mixing evenly to obtain a casting solution;

[0012] S3: Use the casting liquid to lay a film on the support wire mesh, then immerse the support wire mesh in a coagulation bath for solidification, and obtain a finished diaphragm after washing.

[0013] Specifically, the casting solution has the following components by mass: 214-429 parts of organic solvent, 100 parts of alkali-resistant polymer, 0.5-7 parts of pore supporting filler, 10-28 parts of organic hydrophilic modifier, and 50-75 parts of pore-forming agent.

[0014] Preferably, the specific composition of the casting solution is calculated by weight as follows: 285-357 parts of organic solvent, 100 parts of alkali-resistant polymer, 1-1.5 parts of pore supporting filler, 18-25 parts of organic hydrophilic modifier, and 50-75 parts of pore-forming agent.

[0015] Specifically, the alkali-resistant polymer is polysulfone or a modified form of polysulfone, preferably polysulfone.

[0016] Specifically, the pore supporting material is one or more of graphene sheets, carbon nanotubes and carbon quantum dots, preferably graphene sheets.

[0017] Specifically, the organic hydrophilic modifier is one or more of fatty alcohol polyoxyethylene ether, polyoxyethylene alkylamide, oleic acid polyoxyethylene ether, sodium fatty acid methyl ester ethoxylate sulfonate, and alkylphenol polyoxyethylene ether.

[0018] Specifically, the pore-forming agent is polyvinyl pyrrolidone and / or polyethylene glycol.

[0019] Specifically, the solution of the coagulation bath is one or more of deionized water, NMP, DMAC, ethanol, and methanol; the temperature of the coagulation bath is 25 to 90°C, preferably 45 to 60°C.

[0020] The invention also discloses an alkaline water electrolysis hydrogen production diaphragm, which is prepared by the preparation method.

[0021] Compared with the prior art, the present invention can achieve at least one of the following beneficial effects:

[0022] 1. The alkaline water electrolysis hydrogen production diaphragm provided by the present invention has strong alkali resistance, porous structure, low surface resistance, low thickness, good flexibility, no particle peeling, small thickness, good hydrophilicity and wettability, and has great application potential and promotion value.

[0023] The present invention provides a highly hydrophilic and anti-stripping composite alkaline water electrolysis membrane of a polymer system and a preparation method thereof. The membrane is mainly composed of an anti-stretching layer (supporting wire mesh) and a polymer porous layer (see Figure 1 ), the polymer porous layer is formed by phase conversion after the casting liquid enters the coagulation bath. The three-dimensional porous structure of the polymer porous layer can provide good ion permeability while ensuring a certain air tightness.

[0024] The formation process of the polymer porous layer is as follows: first, the uniform casting liquid will form a uniform polymer transition layer on the front and back sides of the support screen. At this time, the porous structure has not yet been formed and the polymer has not been completely solidified, but the pore-forming agent and the pore support material have been evenly distributed in the polymer transition layer. During the coagulation bath process, the polymer transition layer gradually solidifies, and the solvent and pore-forming agent in the polymer transition layer are removed during the coagulation bath and washing process, while the alkali-resistant polymer, pore support material and organic hydrophilic modifier will not be lost or the loss is very small, and then a uniform pore structure appears in the polymer transition layer, and a polymer porous layer is obtained.

[0025] During the preparation of the diaphragm, the alkali-resistant polymer forms the main skeleton of the pores, and the pore-forming agent forms a uniform porous structure on the polymer layer; the pore support material supports the pores to avoid the collapse of the pores after the pore-forming agent is removed in the coagulation bath stage; the present invention also adds an organic hydrophilic modifier, and the functional groups such as ether bonds in the modifier can form hydrogen bonds to enhance the hydrophilicity, so that the polymer porous layer has good hydrophilicity and wetting properties; in addition, the present invention adopts an alkali-resistant support wire mesh to prepare the tensile layer of the diaphragm, which greatly improves the flexibility of the diaphragm and reduces or even avoids the occurrence of diaphragm breakage during transportation or use.

[0026] The present invention adopts a hydrophilic modified polymer system to replace the inorganic nanoparticle filling technology in the prior art, so that the uniformity and stability of the entire diaphragm are greatly improved, and a thinner diaphragm can be produced, thereby achieving lower surface resistance and reducing power loss.

[0027] The thickness of the alkaline water electrolysis hydrogen production diaphragm provided by the present invention can be as low as 100 microns, the infiltration time is less than 0.5s, and the surface resistance can be as low as 0.05Ohn·cm under the test conditions of 25°C and 30% KOH. 2 the following.

[0028] 2. The highly hydrophilic and anti-stripping composite alkaline water electrolysis membrane of the polymer system provided by the present invention has a simple preparation method, and the raw materials and equipment are readily available and the process conditions are mild, which is suitable for large-scale production and wide promotion.

[0029] In the present invention, the above-mentioned technical solutions can also be combined with each other to achieve more preferred combination solutions. Other features and advantages of the present invention will be described in the subsequent description, and some advantages can become obvious from the description, or can be understood by practicing the present invention. The purpose and other advantages of the present invention can be realized and obtained through the contents particularly pointed out in the description and the drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] The drawings are only for the purpose of illustrating particular embodiments and are not to be considered limiting of the present invention. Like reference symbols denote like components throughout the drawings.

[0031] Figure 1 It is a schematic diagram of the structure of the diaphragm for producing hydrogen by alkaline water electrolysis;

[0032] Figure 2 This is a microscopic photograph of the cross section of the diaphragm for hydrogen production by alkaline water electrolysis in Example 1;

[0033] Figure 3 This is a microscopic photograph of the cross section of the diaphragm for hydrogen production by alkaline water electrolysis in Example 2;

[0034] Figure 4 This is a microscopic photograph of the internal pores of the alkaline water electrolysis hydrogen production membrane in Example 1. DETAILED DESCRIPTION

[0035] The preferred embodiments of the present invention are described in detail below in conjunction with the accompanying drawings, wherein the accompanying drawings constitute a part of this application and are used together with the embodiments of the present invention to illustrate the principles of the present invention, but are not used to limit the scope of the present invention.

[0036] After extensive literature research, the inventors found that the current composite membranes used for alkaline hydrolysis to produce hydrogen still have the following problems and shortcomings. Through a large amount of experimental exploration and theoretical analysis, the inventors accurately located the causes and mechanisms of the defects.

[0037] Defect location:

[0038] At present, the alkaline electrolysis hydrogen production diaphragm mainly adopts PPS fabric diaphragm or inorganic-polymer composite diaphragm, among which PPS fabric diaphragm is represented by Toray, and the patent with publication number CN 113201839A introduces this scheme in detail, but PPS fabric diaphragm has problems such as low air tightness and high surface resistance. Inorganic-polymer composite diaphragm is mainly prepared by compounding hydrophilic inorganic nanoparticles such as zirconium oxide, cerium oxide, etc. with polysulfone (PSF), polyetheretherketone (PEEK), polyphenylene sulfide (PPS) fabric, and preparing diaphragm materials with porous structure through phase conversion. Patents with publication numbers CN 116695175A, CN 117004990A, CN116813957A, CN 114561654A, etc. are all prepared based on the above scheme. However, since it is necessary to ensure that the composite diaphragm has good hydrophilic and wetting properties, a large amount of inorganic particles need to be added to the diaphragm. The preferred proportion of inorganic particles even exceeds 70%, resulting in limited fixation ability of the polymer on inorganic matter in the composite diaphragm. The inorganic particles may peel off during actual use, and the excessively high proportion of inorganic particles makes the film brittle and reduces its toughness. It is easy to break and be damaged during transportation and diaphragm installation, thus causing the diaphragm to be scrapped. The thickness of the diaphragm is also limited, mostly around 500 microns, and it is impossible to prepare it thinner, which in turn leads to the inability to obtain a lower surface resistance.

[0039] Mechanism analysis:

[0040] (1) The proportion of polymer substrate in the composite diaphragm is small, while the proportion of inorganic hydrophilic particles is high. The proportion of inorganic particles in the dry film is as high as 65-85%. Although the addition of inorganic hydrophilic particles improves the hydrophilicity and alkali permeability of the diaphragm, it is difficult for the polymer substrate to fix all the inorganic particles. In actual use, inorganic particles often peel off from the inside of the diaphragm, affecting the stable operation of the water electrolysis hydrogen production cell. However, if the proportion of inorganic hydrophilic particles is reduced or the proportion of polymer is increased, the hydrophilic performance will be seriously reduced, the pore structure will be destroyed, the surface resistance will increase sharply, and the ionic conductivity will decrease.

[0041] (2) Since the polymer accounts for a relatively small proportion in the composite diaphragm and inorganic particles account for the majority, the composite diaphragm has poor bending resistance. Excessive bending and bumping will cause cracks, and it is easy to cause damage during assembly and transportation, making the diaphragm unusable.

[0042] (3) Due to the high proportion of inorganic matter, the brittleness and toughness of the diaphragm are poor, which limits the thickness of the diaphragm. The thickness of most diaphragms is limited to 400-800 microns, and it is impossible to prepare diaphragms with thinner thickness and lower surface resistance.

[0043] The invention discloses a method for preparing a diaphragm for producing hydrogen by alkaline water electrolysis, wherein a supporting screen is paved with a film casting liquid and then subjected to a coagulation bath to obtain the diaphragm;

[0044] Wherein, the support wire mesh is woven from alkali-resistant high-strength polymer monofilaments; the main component of the support wire mesh is polyphenylene sulfide (pps) or polyetheretherketone (peek), the weaving density is between 20 mesh and 100 mesh, and the diameter of the monofilament is between 30 microns and 150 microns; the support wire mesh has two main functions, one is to provide tensile strength for the diaphragm, and the other is to support the porous layer internally to enhance its resistance to air pressure and hydraulic pressure. PEEK and PSS are the two most commonly used alkali-resistant engineering plastics with super mechanical properties, among which PPS is cheaper and more cost-effective as the preferred choice. The monofilament diameter of the support wire mesh is lower and the weaving density is higher. The weaving density and diameter of the wire mesh should match the thickness of the diaphragm. When the weaving density and monofilament diameter meet the above requirements, the comprehensive performance of the support wire mesh is better.

[0045] The casting solution contains an organic solvent, an alkali-resistant polymer, a pore supporting filler, an organic hydrophilic modifier and a pore-forming agent.

[0046] Specifically, the casting solution has the following components by mass: 214-429 parts of organic solvent, 100 parts of alkali-resistant polymer, 0.5-7 parts of pore supporting filler, 10-28 parts of organic hydrophilic modifier, and 50-75 parts of pore-forming agent.

[0047] Preferably, the specific composition of the casting solution is calculated by weight as follows: 285-357 parts of organic solvent, 100 parts of alkali-resistant polymer, 1-1.5 parts of pore supporting filler, 18-25 parts of organic hydrophilic modifier, and 50-75 parts of pore-forming agent.

[0048] Organic solvent: Organic solvent plays a role in dissolving components such as polymers and pore-forming agents, and dispersing supporting fillers. Too little solvent will make it more difficult to dissolve the polymer, the viscosity of the casting liquid will be too high and the fluidity will be poor, making it unsuitable for scraping. The washing of the finished film will be more difficult, and the pore structure will be reduced, affecting the ion permeability. Too much solvent will cause material waste, the fluidity of the casting liquid will be too high, the thickness of the film layer cannot be guaranteed, and the morphology of the porous layer cannot be maintained after phase conversion. It is more appropriate when the amount of organic solvent added is 14 to 429 parts, preferably 285 to 357 parts. Specifically, the organic solvent is one or more of N-methylpyrrolidone (NMP), dimethylacetamide (DMAC) or other polar solvents that can dissolve the above-mentioned alkali-resistant polymers, organic hydrophilic modifiers and pore-forming agents, preferably NMP, which has the best dissolution effect.

[0049] Alkali-resistant polymer: Alkali-resistant polymer serves as the matrix of the porous layer, and its content is exactly opposite to that of the solvent. If the content is too high, it will be more difficult to dissolve the polymer, the viscosity of the casting liquid will be too high, and the fluidity will be poor, making it unsuitable for scraping. The washing of the finished membrane will be more difficult, and the pore structure will be reduced, affecting the ion permeability. If the content is too little, the fluidity will be too high, and the casting liquid will have too high a fluidity, making it impossible to guarantee the thickness of the membrane layer, and the morphology of the porous layer cannot be maintained after phase conversion.

[0050] Specifically, the alkali-resistant polymer is polysulfone or a modified form of polysulfone, preferably polysulfone. Polysulfone has significant advantages as a raw material for alkaline water electrolysis hydrogen production membrane, such as high alkali resistance, good mechanical properties, and dimensional stability at high temperatures. And compared with other high-performance materials, polysulfone provides a good balance between cost and performance, making it more economical in large-scale applications.

[0051] In the present invention, the contents of other components are adjusted based on the alkali-resistant polymer, so the mass parts of the alkali-resistant polymer added are uniformly 100 parts.

[0052] Pore ​​support filler: ensures the strength of the porous structure and maintains the porous structure morphology during phase conversion and actual machine production. If the content is too little, the porous structure strength cannot be guaranteed. If the content is too high, the rigidity of the diaphragm is too high, it becomes brittle and loses toughness. When the amount of pore support filler added is 0.5 to 7 parts, the comprehensive performance of the diaphragm is better, preferably 1 to 1.5 parts.

[0053] Specifically, the pore support material is one of graphene sheets, carbon nanotubes and carbon quantum dots, preferably graphene sheets. Carbon nanomaterials can improve the rigidity and mechanical properties of the modified substance with a small amount of addition, and graphene sheets are better than carbon nanotubes and carbon quantum dots in terms of pore support material performance, so graphene sheets are preferred.

[0054] Organic hydrophilic modifier: improves the hydrophilic wettability of the diaphragm. If the content is too low, the hydrophilic wettability is insufficient. If the content is too high, the polymer cannot be fixed and will precipitate from the main alkali-resistant polymer. When the amount of hydrophilic modifier added is 10 to 28 parts, the comprehensive performance of the diaphragm is better, preferably 18 to 25 parts. Specifically, the organic hydrophilic modifier is one or more of fatty alcohol polyoxyethylene ether, polyoxyethylene alkylamide, oleic acid polyoxyethylene ether, fatty acid methyl ester ethoxylate sodium sulfonate, and alkylphenol polyoxyethylene ether.

[0055] Pore-forming agent: Pore-forming agent. If the content is too low, a sufficient number and size of pore structures cannot be prepared. If the content is too high, the pores are too large or the structural strength is insufficient. When the amount of pore-forming agent added is 50 to 75 parts, the comprehensive performance of the diaphragm is better. Specifically, the pore-forming agent is polyvinyl pyrrolidone and / or polyethylene glycol. Experience and experimental tests show that these two pore-forming agents have better pore-forming effects.

[0056] Synergistic effect: The present invention provides a highly hydrophilic and anti-stripping composite alkaline water electrolysis membrane of a polymer system and a preparation method thereof. The membrane is mainly composed of an anti-stretching layer (supporting wire mesh) and a polymer porous layer (see Figure 1 ), the polymer porous layer is formed by phase conversion after the casting liquid enters the coagulation bath. The three-dimensional porous structure of the polymer porous layer can provide good ion permeability while ensuring a certain air tightness.

[0057] The formation process of the polymer porous layer is as follows: first, the uniform casting liquid will form a uniform polymer transition layer on the front and back sides of the support screen. At this time, the porous structure has not yet been formed and the polymer has not been completely solidified, but the pore-forming agent and the pore support material have been evenly distributed in the polymer transition layer. During the coagulation bath process, the polymer transition layer gradually solidifies, and the solvent and pore-forming agent in the polymer transition layer are removed during the coagulation bath and washing process, while the alkali-resistant polymer, pore support material and organic hydrophilic modifier will not be lost or the loss is very small, and then a uniform pore structure appears in the polymer transition layer, and a polymer porous layer is obtained.

[0058] During the preparation of the diaphragm, the alkali-resistant polymer forms the main skeleton of the pores, and the pore-forming agent forms a uniform porous structure on the polymer layer; the pore support material supports the pores to avoid the collapse of the pores after the pore-forming agent is removed in the coagulation bath stage; the present invention also adds an organic hydrophilic modifier, and the functional groups such as ether bonds in the modifier can form hydrogen bonds to enhance the hydrophilicity, so that the polymer porous layer has good hydrophilicity and wetting properties; in addition, the present invention adopts an alkali-resistant support wire mesh to prepare the tensile layer of the diaphragm, which greatly improves the flexibility of the diaphragm and reduces or even avoids the occurrence of diaphragm breakage during transportation or use.

[0059] The present invention adopts a hydrophilic modified polymer system to replace the inorganic nanoparticle filling technology in the prior art, so that the uniformity and stability of the entire diaphragm are greatly improved, and a thinner diaphragm can be produced, thereby achieving lower surface resistance and reducing power loss.

[0060] The preparation method comprises the following specific steps:

[0061] S1: preparing a support screen and measuring an organic solvent, an alkali-resistant polymer, a pore support filler, an organic hydrophilic modifier, and a pore-forming agent according to a preset formula;

[0062] S2: dissolving the pore-forming agent in an organic solvent, slowly adding the pore support material under ultrasonic and stirring conditions to make it uniformly dispersed without sedimentation; adding an alkali-resistant polymer and ensuring that it is completely dissolved; finally adding an organic hydrophilic modifier and mixing evenly to obtain a casting solution;

[0063] S3: Use the casting liquid to lay a film on the support wire mesh, then immerse the support wire mesh in a coagulation bath for solidification, and obtain a finished diaphragm after washing.

[0064] It is worth noting that the specific parameters of step S2 are: ultrasonic frequency above 40khz, power above 300w, stirring rate between 300rpm-1000rpm. Among them, pore-forming agents such as polyvinyl pyrrolidone (PVP) not only play the role of pore-forming agents, but also are excellent dispersants for carbon materials such as graphene sheets and carbon nanotubes. Dissolving pore-forming agents such as PVP first can play a good dispersing effect on these materials, and the viscosity of the solution increases after polysulfone is dissolved, which is not conducive to the uniform dispersion of materials such as graphene and carbon nanotubes. Therefore, the dissolution order is: pore-forming agents such as PVP, pore support materials such as graphene, alkali-resistant polymers such as polysulfone, organic hydrophilic agents, etc. (the organic hydrophilic agent is placed last to reduce the influence on the dispersion or dissolution of the previous material).

[0065] It is worth emphasizing that during the film laying process (generally using a scraper), care should be taken to ensure that the supporting screen is completely immersed in the film casting liquid, but it does not need to be in the middle; in particular, it should be avoided that the screen peels off or is exposed after the film is laid, otherwise it will affect the overall performance of the diaphragm. The film laying thickness mainly includes two requirements. On the one hand, the supporting screen must be completely covered, and on the other hand, it is necessary to provide the diaphragm with sufficient air tightness and pressure resistance. Measured by the bubble point, the thicker the film, the higher the bubble point, the better the air tightness and pressure resistance, but the thicker the thickness, the worse the ion permeability, and the greater the power loss during hydrogen electrolysis. Combining the above two points and the current process level, the thickness of the diaphragm should be between 100 and 500 microns.

[0066] There are no special requirements for the washing process. The main purpose is to clean the solvent, pore-forming agent, and unfixed hydrophilic agent and pore supporting material in the diaphragm. The requirements are that the washing should be clean and the temperature should not be too high to cause excessive dimensional shrinkage. In summary, the washing temperature is between 60 and 90°C, preferably 80°C.

[0067] Specifically, the solution of the coagulation bath is one or more of deionized water, NMP, DMAC, ethanol, and methanol; the coagulation bath temperature is 25-90° C., preferably 45-60° C. The solution and temperature selection mainly affect the pore morphology and phase conversion efficiency, and are mutually matched and corresponding to the front-end casting solution formula. It has been verified by experiments that the above conditions are more favorable for the formation of pores.

[0068] The present invention also discloses an alkaline water electrolysis hydrogen production diaphragm, which is prepared by the above preparation method. The diaphragm has the advantages of bending resistance, peeling resistance, high hydrophilicity (wetting property), low surface resistance and small thickness. The minimum thickness can reach 100 microns, the wetting time is less than 0.5s, and the surface resistance can be as low as 0.05Ohn·cm under the test conditions of 25℃ 5% KOH. 2 the following.

[0069] Example 1

[0070] Preparation of 140 micron (default) thickness diaphragm:

[0071] Weigh 80g of polyvinyl pyrrolidone and dissolve it in 450g of NMP. Slowly add 2.75g of graphene sheets under ultrasound (40kHz, 300W) and stirring conditions (500rpm) to uniformly disperse them in the solvent without settling. Add 150g of polysulfone and ensure complete dissolution. Add 25g of fatty alcohol polyoxyethylene ether, 3g of oleic acid polyoxyethylene ether, and 2g of fatty acid methyl ester ethoxylate sodium sulfonate and mix well to obtain a casting solution.

[0072] A 75-mesh, 70-micron polyphenylene sulfide monofilament screen was selected, the scraper height limit was adjusted to 160 microns, and the film was scraped using the configured casting liquid. After the film was scraped, it was allowed to stand for about 15 seconds, and the screen with the film was directly immersed in a coagulation bath for curing. The coagulation bath was configured to a temperature of 45°C, and the coagulation bath solution was a mixed solution of deionized water and ethanol. The volume ratio of deionized water and ethanol was 7:3. After 5 minutes of complete curing, the diaphragm was transferred to 80°C deionized water and thoroughly washed to obtain the finished product.

[0073] Example 2

[0074] Preparation of 320 micron (default value) diaphragm:

[0075] Weigh 80g of polyvinyl pyrrolidone and dissolve it in 450g of NMP. Slowly add 3.0g of graphene sheets under ultrasound (40kHz, 300W) and stirring conditions (500rpm) to make them evenly dispersed in the solvent without sedimentation. Add 140g of polysulfone and ensure complete dissolution. Add 25g of fatty alcohol polyoxyethylene ether, 4g of oleic acid polyoxyethylene ether, and 3g of fatty acid methyl ester ethoxylate sodium sulfonate and mix well to obtain a casting solution.

[0076] A 50-mesh, 120-micron polyphenylene sulfide monofilament screen was selected, the scraper height limit was adjusted to 360 microns, and the film was scraped using the configured casting liquid. After the film was scraped, it was allowed to stand for about 15 seconds, and the screen with the film was directly immersed in a coagulation bath for curing. The coagulation bath was configured to a temperature of 60°C, and the coagulation bath solution was a mixed solution of deionized water and ethanol. The volume ratio of deionized water to ethanol was 6:4. After 5 minutes of complete curing, the diaphragm was transferred to 80°C deionized water and thoroughly washed to obtain the finished product.

[0077] Example 3

[0078] Preparation of 100 micron (default value) diaphragm:

[0079] Weigh 80g of polyvinyl pyrrolidone and dissolve it in 450g of NMP. Slowly add 3.5g of graphene sheets under ultrasound (40kHz, 300W) and stirring conditions (500rpm) to uniformly disperse them in the solvent without sedimentation. Add 160g of polysulfone and ensure complete dissolution. Add 30g of fatty alcohol polyoxyethylene ether, 5g of oleic acid polyoxyethylene ether, and 4g of fatty acid methyl ester ethoxylate sodium sulfonate and mix well to obtain a casting solution.

[0080] Select a 100-mesh, 50-micron polyphenylene sulfide monofilament screen, adjust the scraper height limit to 135 microns, use the configured casting liquid to scrape the film, let it stand for about 15 seconds after scraping, and directly immerse the screen after film formation in a coagulation bath for curing. The coagulation bath is configured to a temperature of 60°C, and the coagulation bath solution is a mixed solution of deionized water and ethanol. The volume ratio of deionized water and ethanol is 8:2. After 5 minutes of complete curing, the diaphragm is transferred to 80°C deionized water and thoroughly washed to obtain the finished product.

[0081] Example 4

[0082] Preparation of 500 micron (default value) diaphragm:

[0083] Weigh 80g of polyvinyl pyrrolidone and dissolve it in 450g of NMP. Slowly add 2.75g of graphene sheets under ultrasound (40kHz, 300W) and stirring conditions (500rpm) to make it evenly dispersed in the solvent without sedimentation. Add 125g of polysulfone and ensure complete dissolution. Add 22g of fatty alcohol polyoxyethylene ether, 3g of oleic acid polyoxyethylene ether, and 2.5g of fatty acid methyl ester ethoxylate sodium sulfonate and mix well to obtain a casting solution.

[0084] A 30-mesh, 120-micron polyphenylene sulfide monofilament screen was selected, the scraper height limit was adjusted to 540 microns, and the film was scraped using the prepared casting liquid. After the film was scraped, it was allowed to stand for about 15 seconds, and the screen with the film was directly immersed in a coagulation bath for curing. The coagulation bath was configured to a temperature of 80°C, and the coagulation bath solution was a mixed solution of deionized water and ethanol. The volume ratio of deionized water to ethanol was 5:5. After 5 minutes of complete curing, the diaphragm was transferred to 90°C deionized water and thoroughly washed to obtain the finished product.

[0085] Example 5

[0086] Preparation of 200 micron (default value) diaphragm:

[0087] Weigh 80g of polyvinyl pyrrolidone and dissolve it in 450g of NMP. Slowly add 3.0g of graphene sheets under ultrasound (40kHz, 300W) and stirring conditions (500rpm) to make them evenly dispersed in the solvent without sedimentation. Add 140g of polysulfone and ensure complete dissolution. Add 28g of fatty alcohol polyoxyethylene ether, 4g of oleic acid polyoxyethylene ether, and 3g of fatty acid methyl ester ethoxylate sodium sulfonate and mix well to obtain a casting solution.

[0088] A 75-mesh, 70-micron polyphenylene sulfide monofilament screen was selected, the scraper height limit was adjusted to 360 microns, and the film was scraped using the configured casting liquid. After the film was scraped, it was allowed to stand for about 15 seconds, and the screen with the film was directly immersed in a coagulation bath for curing. The coagulation bath was configured to a temperature of 60°C, and the coagulation bath solution was a mixed solution of deionized water and ethanol. The volume ratio of deionized water to ethanol was 6:4. After 5 minutes of complete curing, the diaphragm was transferred to 80°C deionized water and thoroughly washed to obtain the finished product.

[0089] Comparative Example 1

[0090] 500 microns (preset value) Preparation of traditional inorganic particle-containing membrane:

[0091] 80 g of polyvinyl pyrrolidone was weighed and dissolved in 450 g of NMP, 125 g of polysulfone was added and ensured to be completely dissolved, 300 g of zirconium oxide was added and mixed evenly to obtain a casting solution.

[0092] Select a 30-mesh, 120-micron polyphenylene sulfide monofilament screen, adjust the scraper height limit to 540 microns, use the configured casting liquid to scrape the film, let it stand for about 15 seconds after scraping, and directly immerse the screen after film formation in a coagulation bath for curing. The coagulation bath is configured to a temperature of 25°C, and the coagulation bath solution is deionized water. After 5 minutes of complete curing, transfer the diaphragm to 80°C deionized water and thoroughly wash it to obtain the finished product.

[0093] Comparative Example 2

[0094] 320 micron (default value) diaphragm preparation without adding hydrophilic components:

[0095] Weigh 80 g of polyvinyl pyrrolidone and dissolve it in 450 g of NMP. Slowly add 3.0 g of graphene sheets under ultrasonic (40 kHz, 300 W) and stirring conditions (500 rpm) to make it evenly dispersed in the solvent without sedimentation. Add 140 g of polysulfone and ensure complete dissolution to obtain a casting solution.

[0096] A 50-mesh, 120-micron polyphenylene sulfide monofilament screen was selected, the scraper height limit was adjusted to 360 microns, and the film was scraped using the configured casting liquid. After the film was scraped, it was allowed to stand for about 15 seconds, and the screen with the film was directly immersed in a coagulation bath for curing. The coagulation bath was configured to a temperature of 60°C, and the coagulation bath solution was a mixed solution of deionized water and ethanol. The volume ratio of deionized water to ethanol was 6:4. After 5 minutes of complete curing, the diaphragm was transferred to 80°C deionized water and thoroughly washed to obtain the finished product.

[0097] Comparative Example 3

[0098] 320 micron (default value) diaphragm preparation without adding pore support material:

[0099] Weigh 80g of polyvinyl pyrrolidone and dissolve it in 450g of NMP to evenly disperse it in the solvent without settling, add 140g of polysulfone and ensure complete dissolution, add 28g of fatty alcohol polyoxyethylene ether, 4g of oleic acid polyoxyethylene ether, and 3g of fatty acid methyl ester ethoxylate sodium sulfonate and mix well to obtain a casting solution.

[0100] A 50-mesh, 120-micron polyphenylene sulfide monofilament screen was selected, the scraper height limit was adjusted to 360 microns, and the film was scraped using the configured casting liquid. After the film was scraped, it was allowed to stand for about 15 seconds, and the screen with the film was directly immersed in a coagulation bath for curing. The coagulation bath was configured to a temperature of 60°C, and the coagulation bath solution was a mixed solution of deionized water and ethanol. The volume ratio of deionized water to ethanol was 6:4. After 5 minutes of complete curing, the diaphragm was transferred to 80°C deionized water and thoroughly washed to obtain the finished product.

[0101] Comparative Example 4

[0102] 320 microns (default value) excess hydrophilic modifier:

[0103] Weigh 80 g of polyvinyl pyrrolidone and dissolve it in 450 g of NMP. Slowly add 3.0 g of graphene sheets under ultrasound (40 kHz, 300 W) and stirring conditions (500 rpm) to uniformly disperse them in the solvent without settling. Add 140 g of polysulfone and ensure complete dissolution. Add 50 g of fatty alcohol polyoxyethylene ether, 10 g of oleic acid polyoxyethylene ether, and 8 g of fatty acid methyl ester ethoxylate sodium sulfonate and mix well to obtain a casting solution.

[0104] A 50-mesh, 120-micron polyphenylene sulfide monofilament screen was selected, the scraper height limit was adjusted to 360 microns, and the film was scraped using the configured casting liquid. After the film was scraped, it was allowed to stand for about 15 seconds, and the screen with the film was directly immersed in a coagulation bath for curing. The coagulation bath was configured to a temperature of 60°C, and the coagulation bath solution was a mixed solution of deionized water and ethanol. The volume ratio of deionized water to ethanol was 6:4. After 5 minutes of complete curing, the diaphragm was transferred to 80°C deionized water and thoroughly washed to obtain the finished product.

[0105] The bubble point test is conducted in accordance with GB / T 32361-2015. The surface resistance test is conducted in accordance with SJ / T10171-2016 at 25°C and 30% KOH. The washing condition is the observation result after the finished film is washed in deionized water at 60°C for 15 minutes. The folding times are tested with the MIT instrument in accordance with GB / T457-2008, with a bending angle of 135±2° and a load of 9.81N. When cracks visible to the naked eye appear on the diaphragm, it is judged as failure. The more folding times, the stronger the folding performance.

[0106] Table 1 Comprehensive performance of diaphragms in various embodiments and comparative examples

[0107]

[0108] According to Examples 1 to 5, the thinner the film thickness, the lower the surface resistance, but the air tightness also decreases. For the actual design pressure and actual installation method of the electrolytic cell, the film thickness is preferably 100-500 microns. Overall, the diaphragm provided by the present invention has an infiltration time of less than 2s and a surface resistance of ≤0.22Ohn·cm 2 , almost no peeling phenomenon.

[0109] According to Comparative Example 1, compared with the conventional 500 micron diaphragm with zirconium oxide as the hydrophilic main body, the diaphragm provided by the present application not only has no problem of easy peeling, but also can achieve a thinner thickness and lower surface resistance. In addition, since no inorganic particles are added, the bending resistance of the diaphragm is also significantly enhanced, and it can withstand 135° and more than 500 bends without obvious cracks.

[0110] It can be seen from Comparative Example 2 and Example 2 that when no hydrophilic modifier is added, the surface resistance of the diaphragm increases sharply, indicating that the hydrophilic modifier plays an important role in the diaphragm.

[0111] It can be seen from Example 2 and Comparative Example 3 that pore collapse occurs inside the diaphragm without adding pore proppant, resulting in a rapid decrease in the number of micropores available for ion passage and a sharp increase in surface resistance.

[0112] It can be seen from Comparative Example 4 and Example 2 that excessive addition of hydrophilic agent will not increase the surface resistance of the diaphragm, but will cause the polymer to be unable to fix the hydrophilic agent and precipitate. The precipitation of the hydrophilic agent is an important defect in actual implementation. Therefore, the content ratio of the hydrophilic agent needs to be maintained within a reasonable range.

[0113] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily conceived by any technician familiar with the technical field within the technical scope disclosed by the present invention should be covered within the protection scope of the present invention.

Claims

1. A method for preparing a diaphragm for producing hydrogen by alkaline water electrolysis, characterized in that: The support wire mesh is paved with a casting liquid and then subjected to a coagulation bath to obtain the diaphragm; wherein the support wire mesh is woven from alkali-resistant high-strength polymer monofilaments; the casting liquid contains an organic solvent, an alkali-resistant polymer, a pore support filler, an organic hydrophilic modifier, and a pore-forming agent; The pore supporting filler supports the pores to prevent the pores from collapsing after the pore-forming agent is removed during the coagulation bath stage; The organic hydrophilic modifier enables the polymer porous layer to have good hydrophilicity and wettability; The organic hydrophilic modifier is one or more of fatty alcohol polyoxyethylene ether, polyoxyethylene alkylamide, oleic acid polyoxyethylene ether, sodium fatty acid methyl ester ethoxylate sulfonate, and alkylphenol polyoxyethylene ether; The specific composition of the casting solution is calculated by weight: 214-429 parts of organic solvent, 100 parts of alkali-resistant polymer, 0.5-7 parts of pore supporting filler, 10-28 parts of organic hydrophilic modifier, and 50-75 parts of pore-forming agent.

2. The preparation method according to claim 1, characterized in that: The specific steps include: S1: preparing a support screen and measuring an organic solvent, an alkali-resistant polymer, a pore support filler, an organic hydrophilic modifier, and a pore-forming agent according to a preset formula; S2: dissolving the pore-forming agent in an organic solvent, slowly adding the pore-supporting filler under ultrasonic and stirring conditions to make it uniformly dispersed without settling; adding an alkali-resistant polymer and ensuring that it is completely dissolved; finally adding an organic hydrophilic modifier and mixing evenly to obtain a casting solution; S3: Use the casting liquid to lay a film on the support wire mesh, then immerse the support wire mesh in a coagulation bath for solidification, and obtain a finished diaphragm after washing.

3. The preparation method according to claim 1, characterized in that: The specific composition of the casting solution is calculated by weight: 285-357 parts of organic solvent, 100 parts of alkali-resistant polymer, 1-1.5 parts of pore supporting filler, 18-25 parts of organic hydrophilic modifier, and 50-75 parts of pore-forming agent.

4. The preparation method according to claim 1, characterized in that: The alkali-resistant polymer is polysulfone or a modified form of polysulfone.

5. The preparation method according to claim 1, characterized in that: The pore supporting filler is graphene sheet and / or carbon nanotube.

6. The preparation method according to claim 1, characterized in that: The pore-forming agent is polyvinyl pyrrolidone and / or polyethylene glycol.

7. The preparation method according to claim 2, characterized in that: The solution of the coagulation bath is one or more of deionized water, NMP, DMAC, ethanol and methanol; the temperature of the coagulation bath is 25-90°C.

8. An alkaline water electrolysis hydrogen production diaphragm, characterized in that: The diaphragm is prepared by the preparation method according to any one of claims 1 to 7.

Citation Information

Patent Citations

  • Polyphenylene sulfide fabric for water electrolyser as well as preparation method and application of polyphenylene sulfide fabric

    CN113201839A

  • Composite diaphragm for water electrolyser

    CN116377508A

  • Water electrolysis hydrogen production super-hydrophilic diaphragm and preparation method thereof

    CN117089887A